Transformasi Estetika Seni Tari Tradisional dalam Konteks Pertunjukan Modern: Antara Visualitas dan Makna - Wibisono, Namira Allegra (Jurnal Cerano Seni : Pengkajian dan Penciptaan Seni Pertunjukan, 2026)
Background of this research is the phenomenon of aesthetic transformation of Indonesian traditional dance in the context of modern performances that demand the reinforcement of visuality aspects, yet potentially shift the cultural, spiritual, and symbolic meanings inherent in the dance. Objectives of this research are to analyze the forms of visuality transformation in modern traditional dance performances, to describe the impact of visuality transformation on the meaning of traditional dance, and to map the relationship between visuality and meaning in contemporary performance practices. Methods this research employs a systematic literature review (SLR) with the PRISMA protocol. Data collection was conducted through literature searches on Publish or Perish and Google Scholar databases using the keywords "Seni Tari Tradisional", "Traditional Dance", "Aesthetic Transformation", and "Visual Perform" within the 2016-2026 timeframe. Data analysis used thematic synthesis. Findings reveal that visuality transformation occurs through compression of movement structures, costume innovation, musical hybridity, and digital representation. The meaning of dance undergoes shifts from sacred functions to entertainment, reinterpretation of gender values, adaptation to religious values, and preservation of customary meanings. The relationship between visuality and meaning is spectral: complementary, contradictory, and ambivalent. Conclusions of this research indicate that aesthetic transformation is an adaptive mechanism that allows traditional dance to remain relevant, with the success of transformation measured by the extent to which the essence of meaning remains recognized and inherited by the cultural community.